2018
DOI: 10.1029/2018jb016003
|View full text |Cite
|
Sign up to set email alerts
|

Sorption‐Induced Deformation and Elastic Weakening of Bentheim Sandstone

Abstract: A number of studies show that adsorption of small amount of water causes significant reduction of elastic moduli and increase of elastic wave attenuation in sandstones. This effect is of practical importance for near‐surface seismic studies and for applications of conventional rock physics theories, which require measurements of elastic properties of dry rock. Additionally, adsorption of water causes deformation of porous materials and rocks, which can be explained by the concept of varying surface stress, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 54 publications
6
37
1
Order By: Relevance
“…Earlier works showed that strong softening could occur upon moisture adsorption in sandstones (Clark et al, ) and that it was not an effect of the clay minerals as particularly strong effects could be obtained in quartz‐pure sandstones (Pimienta, Fortin, & Gueguen, ). As further reported in the literature, elastic softening was found to correlate with the amplitude loss and thus P wave attenuation, which is consistent with what is observed here (Clark et al, ; Pimienta, Fortin, & Gueguen, ; Tittmann, Clark, Richardson, et al, ; Yurikov et al, ). Existing dissipative effects that could be considered are the frequency‐dependent squirt flow (e.g., Gurevich et al, ) or frequency‐independent dissipation at grain contact (e.g.…”
Section: Interpretationssupporting
confidence: 92%
“…Earlier works showed that strong softening could occur upon moisture adsorption in sandstones (Clark et al, ) and that it was not an effect of the clay minerals as particularly strong effects could be obtained in quartz‐pure sandstones (Pimienta, Fortin, & Gueguen, ). As further reported in the literature, elastic softening was found to correlate with the amplitude loss and thus P wave attenuation, which is consistent with what is observed here (Clark et al, ; Pimienta, Fortin, & Gueguen, ; Tittmann, Clark, Richardson, et al, ; Yurikov et al, ). Existing dissipative effects that could be considered are the frequency‐dependent squirt flow (e.g., Gurevich et al, ) or frequency‐independent dissipation at grain contact (e.g.…”
Section: Interpretationssupporting
confidence: 92%
“…To better understand the observed phenomena, the hypothesis that solvation pressure induced by adsorption of water in the microstructure is responsible for the elastic weakening Figure 7: S-wave velocity and swelling strains for the Thüringer sandstone over 1 cycle of RH variations Figure 8: S-wave velocity Vs within Thüringer sandstone during the seven cycles of moisture variations from 25% to 97% of relative humidity (dot section is extrapolated for the fourth cycle) in black line, and RH variations in grey line identified, is considered. In their paper, [Yurikov et al, 2018] calculate the fluid pressure using the following equation, adapted for our notation:…”
Section: Elastic Weakening and Solvation Pressurementioning
confidence: 99%
“…Elastic properties evolution with saturation and moisture content has also been highlighted [Sarout, 2006,Vasarhelyi, 2003,Valès, 2008,Erguler and Ulusay, 2009,Pimienta et al, 2014. The relationship between the evolution of the elastic moduli during adsorption and the deformation of the stone is of main interest to better understand elastic weakening [Yurikov et al, 2018]. Moreover, this phenomenon depends on the amount and nature of clay minerals within the stone, since they are more reactive to water [Nara et al, 2011, Nara et al, 2012, Funatsu et al, 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A way through which adsorption can modify the mechanical properties of the adsorbent is through its impact on the microstructure: Perrier et al [33] showed that, in microporous materials, the apparent porosity can vary significantly upon the adsorption, and hence impact the poroelastic properties of the material. For a sandstone, whose dry mechanical behavior is nonlinear, variations of the elastic moduli with relative humidity could be explained by the impact of the variation of relative humidity on solvation pressure and hence effective stress [34]. Note however that, even in absence of nonlinearity or rearrangement of the microstructure, adsorption can impact the drained moduli of the porous material [29].…”
Section: Impact Of Adsorption On Mechanical Propertiesmentioning
confidence: 99%